METODOLOGI PENAFSIRAN SAID NURSI DALAM KITAB ISYARAT AL-I’JAZ FI MAZANN AL-IJAZ - Nasir, M Iqbal; Galib, Muhammad; Firdaus, Firdaus (Jurnal Diskursus Islam, 2018)
Subject matter in this research is how the methodology of interpretation of Said Nursi in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz The purpose of this research is to 1) to know the method of interpretation of Said Nursi in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz, 2) to know the approach to and interpretation of Said Nursi in Isyarat al-I’jaz fi Mazann al-Ijaz, 3) to know the techniques of interpretation of Said Nursi in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz, 4) to know the advantages and limitations of the interpretation of Said Nursi in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz. This type of research is the research library research. Research approach in this research is the approach of science of tafseer. As for the data sources used are primary and secondary sources. The next method of data collection was done by affirming the theme data is searchable, affirmed the source data, do data coding or classification to facilitate the researchers in this study. And techniques of processing and data analysis is performed using data reduction system, data and cereal drawdown conclusion. The results showed that: 1) method of interpretation used Said Nursi in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz is a method of tahlili or analysis, 2) approach is Said Nursi use in Scripture Isyarat al-I’jaz fi Mazann al-Ijaz is the theological approach. And the pattern is the pattern of Isyari,  3) Said Nursi interpretation techniques apply in the book Isyarat al-I’jaz fi Mazann al-Ijaz textual interpretation and technique is contextual, 4) the advantages of book Isyarat al-I’jaz fi Mazann al-Ijaz are: a) the sentence that concisely, b) use three stages in interpreting the Qur'an, verse by verse previous relationships, relationship verse in the form of phrases, the texts in each relationship, c) reveal the secrets and wisdom which contained in every verse of the Qur'an, d) forms of questioning in its interpretation, e) proposes nazm al-Qur'an, f) independently thinking israiliyyat, g) combines several disciplines in interpreting the Qur'an. As for the limitations that are owned are: a) interpreted the surah al-Fatihah and surah al-Baqarah, b) the language used is very elusive, c) understanding book of Isyarat al-I’jaz fi Mazann al-Ijaz limited to people who had the insight a vast, d) does not mention the asbab al-nuzul ayah, e) are not listed the sources reference. The implications of research in this research study is expected to contribute to the academic community in reviewing the methodology of interpretation of which has a significant role in helping understand the Systematics of the scholars in the interpret the verses of the Qur'an.